Easy fabrication of a vibrating foil electrode - Lu, M; Rees, N; Compton, R (2012)
We report a simple, rapid and cost effective fabrication of a vibrating platinum foil electrode whereby significant mass transport enhancement can be seen and applied for electroanalytical work. The vibrating and stationary nature of the platinum foil electrode was characterised by cyclic voltammetry using a Ru(NH 3) 62+/3+ redox system, and a four-fold enhancement in sensitivity could be reproducibly seen. Randles- Ševčik analysis gave a diffusion coefficient, D value, of 9.4 × 10 -6 cm 2 s -1. © 2012 The Royal Society of Chemistry.